Thermal refuge use and parasitism: Spatiotemporal variation in anchor worm and lamprey wounds on Klamath redband trout - Jordan D. Ortega; Nicholas Hahlbeck; Chris Derrickson; William Tinniswood; Taal Levi; Jonathan Armstrong (Ecosphere, 2023)
Abstract Climate warming is increasing maximum temperatures during summer such that they more frequently exceed the thermal tolerances of ectotherms, particularly cold‐water fishes. One way that species can avoid thermal stress is by moving to thermal refuge habitats. Thermal refuges remain suitably cool during summer and are often complementary to foraging, spawning, and rearing habitats. Although the benefits associated with the thermal aspects of refuges are well studied, much less is known about potential costs associated with nonthermal aspects. For example, crowding of cold‐water fishes into seasonal refuge habitats could increase parasite loads and cause declines in fitness. We assessed lamprey and anchor worm parasitism in Upper Klamath Lake where adfluvial redband trout (Oncorhynchus mykiss newberrii) move to thermal refuge habitats during summer. We sampled trout in Upper Klamath Lake during spring and in adjacent thermal refuge habitats during summer. We also evaluated survival as a function of lamprey wounding using motion‐sensing radio tags. There was a fourfold decline in the number of lamprey wounds on trout upon the onset of thermal refuge use. In contrast, cases of severe anchor worm (≥20 sores) increased threefold during thermal refuge use. Survival in thermal refuge was not different for lamprey‐wounded trout than for trout that migrated to thermal refuge without lamprey wounds. We found that both parasites were absent in a lotic population of redband trout downstream that lacked access to thermal refuge. Thus, the effects of seasonal refuge use on parasite load varied depending on the parasite taxon considered and local habitat conditions, implying that managers will likely require empirical data for focal habitats and taxa to understand how parasitism affects thermal refuge use.